Establishment of an in vitro three‐dimensional model for cartilage damage in rheumatoid arthritis - Peck, Yvonne (2020)
Rheumatoid arthritis (RA) is a chronic inflammatory disease that leads to progressive joint destruction. To further understand the process of rheumatoid cartilage damage, an in vitro model consisting of an interactive tri‐culture of synovial fibroblasts (SFs), LPS‐stimulated macrophages and a primary chondrocyte‐based tissue‐engineered construct was established. The tissue‐engineered construct has a composition similar to that of human cartilage, which is rich in collagen type II and proteoglycans. Data generated from this model revealed that healthy chondrocytes were activated in the presence of SFs and macrophages. The activated chondrocytes subsequently displayed aberrant behaviours as seen in a disease state such as increased apoptosis, decreased gene expression for matrix components such as type II collagen and aggrecan, increased gene expression for tissue‐degrading enzymes (MMP‐1, ‐3, ‐13 and ADAMTS‐4, ‐5), and upregulation of inflammatory mediator gene expression (TNF‐α, IL‐1β, IL‐6 and IKBKB). Additionally, the inclusion of SFs and macrophages in the model enabled both cell types to more closely replicate an in vivo role in mediating cartilage destruction. This is evidenced by extensive matrix loss, detected in the model through immunostaining and biochemical analysis. Subsequent drug treatment with celecoxib has shown that the model was able to respond to the therapeutic effects of this drug by reversing cartilage damage. This study showed that the model was able to recapitulate certain pathological features of an RA cartilage. If properly validated, this model potentially can be used for screening new therapeutic drugs and strategies, thereby contributing to the improvement of anti‐rheumatic treatment.